SOSIALISASI DAN STRATEGI JITU PENCEGAHAN PERGAULAN BEBAS DI SEKOLAH DASAR NAGARI 19 KOTO BARU - Noveria, Ena; Zulhafendi, Redy Williantama; Fadillah, Muhammad; Hariman, Subhan Nuredi; Hadi, Irfan Surya; Nadiroha, Widia (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Promiscuity is an increasingly worrying social phenomenon, including among elementary school children. The socialisation of promiscuity prevention at the elementary school level is crucial for building a strong character foundation from an early age. This study aims to improve students' understanding of promiscuity and identify effective strategies for preventing promiscuity in elementary school children. The qualitative research method involved all students at SDN 19 Koto Baru. Data was collected through observation and questioning and analysed using thematic and meta-review methods. The results showed that the majority of students had gained basic knowledge about the dangers of promiscuity, although there were still concerns about peer pressure. These findings provide an important insight for strengthening character education programmes in schools and supporting the role of the family in preventing deviant behaviour from an early age. Therefore, this study recommends that teachers optimise interactive teaching methods, parents increase dialogue and supervision at home, and schools routinely organise socialisation programmes to create a positive social environment conducive to forming strong moral values.